Epicyclic Gear Train Synthesis - Brumercik, Frantisek; Tomasikova, Maria; Nieoczym, Aleksander (Communications - Scientific letters of the University of Zilina, 2015)
The synthesis of an epicyclic gear train is a difficult task that can be solved by different methods with significantly various computational time demands. This article describes effective approach to the two-linked epicyclic gear train synthesis. The method described in this article is based on the fundamental gear ratio calculation for each possible combination of gearbox external elements connected to the internal planetary structure.